2012
DOI: 10.1007/s10824-012-9160-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of having more than one good reputation on distributor investments in the film industry

Abstract: Reputations of organizations and its individual members are valuable resources that help new organizations to get access to investment capital. Reputations, however, can have different dimensions. In this paper, we argue that an individual's reputation along a particular dimension will have a positive effect on the behavior of investors when it is role congruent. In addition, we argue that also scoring favorably on the role-incongruent dimension at the same time-or, in other words, engaging in reputational cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…A commonly held view is that reputation involves "being known for something" (Jensen & Roy, 2008;Lange et al, 2011) and is based on an actor's accomplishments and history (Barron & Rolfe, 2012;Weigelt & Camerer, 1988). 1 Previous studies that have examined the external signals of reputation (Anand & Peterson, 2000;Carter et al, 1998;Ebbers & Wijnberg, 2012;Philippe & Durand, 2011) suggest that reputation reduces uncertainty about an actor's future behavior, which enables evaluators (i.e., an audience) to assess actors (Spence, 1973). A positive reputation is beneficial because it reduces uncertainty and provides reassurance of an actor's value.…”
Section: Audience-specific Reputationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A commonly held view is that reputation involves "being known for something" (Jensen & Roy, 2008;Lange et al, 2011) and is based on an actor's accomplishments and history (Barron & Rolfe, 2012;Weigelt & Camerer, 1988). 1 Previous studies that have examined the external signals of reputation (Anand & Peterson, 2000;Carter et al, 1998;Ebbers & Wijnberg, 2012;Philippe & Durand, 2011) suggest that reputation reduces uncertainty about an actor's future behavior, which enables evaluators (i.e., an audience) to assess actors (Spence, 1973). A positive reputation is beneficial because it reduces uncertainty and provides reassurance of an actor's value.…”
Section: Audience-specific Reputationsmentioning
confidence: 99%
“…Researchers examining various contexts, ranging from product and service markets (Diekmann, Jann, Przepiorka, & Wehrli, 2014;Rindova, Williamson, Petkova, & Sever, 2005) to corporate financing (Carter, Dark, & Singh, 1998;D'Aveni, 1990), stock markets (Pfarrer, Pollock, & Rindova, 2010), entrepreneurial efforts (Pollock & Gulati, 2007;Shane & Cable, 2002), and cultural industries (Delmestri, Montanari, & Usai, 2005;Ebbers & Wijnberg, 2012), have shown that reputation is a valuable intangible asset that increases reputation holders' success (Raub & Weesie, 1990;Shapiro, 1983). Most of this research operates under the assumption that actors have a single overall reputation and, furthermore, that reputation holders interact with an audience with homogenous concerns (Fombrun, 1996;Fombrun & Shanley, 1990;Fombrun & Van Riel, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A seemingly non‐biased method of selection in the music industry is to use success in the singles market to determine whether an artist is qualified to enter the more cost‐intensive albums market (Fox and Kochanowski ). There is also evidence that different funders apply different criteria in their selection processes as to whether artistic or financial reputation is emphasized (Ebbers and Wijnberg , ). Moreover, the power to select may transfer between actors in a value chain (Grantham and Kaplinsky ).…”
Section: Product−market Characteristicsmentioning
confidence: 99%
“…This is done mostly through articles in the mass media, events, or conversations about culture and intellectual society. For example, in the movie industry, because such organizations provide works both that are relevant to this domain of activity and that can make society think and react, expert reputation of movie directors is based on film critics' reviews in mass newspapers that inform and guide the general public (Ebbers and Wijnberg, 2011).…”
Section: Perspectives On Selection Systemmentioning
confidence: 99%